4D-MRI driven MR-guided online adaptive radiotherapy for abdominal stereotactic body radiation therapy on a high field MR-Linac: Implementation and initial clinical experience. (July 2020) - Paulson, Eric S.; Ahunbay, Ergun; Chen, Xinfeng; Mickevicius, Nikolai J.; Chen, Guang-Pei; Schultz, Christopher; Erickson, Beth; Straza, Michael; Hall, William A.; Li, X. Allen
Highlights: This is the first clinical use of 4D-MRI in an online radiation therapy workflow. Eleven patients received SBRT on an Elekta MR-Linac using ATP and ATS workflows. A parallel contour editing approach was successfully utilized in the ATS workflow. Abstract: Background and purpose: In this report, we describe our implementation and initial clinical experience using 4D-MRI driven MR-guided online adaptive radiotherapy (MRgOART) for abdominal stereotactic body radiotherapy (SBRT) on the Elekta Unity MR-Linac. Materials and methods: Eleven patients with abdominal malignancies were treated with free-breathing SBRT in three to five fractions on a 1.5 T MR-Linac. Online adaptive plans were generated using Adapt-To-Position (ATP) or Adapt-To-Shape (ATS) workflows based on motion averaged or mid-position images derived from a pre-beam 4D-MRI. A high performance server positioned on the local MR-Linac machine network was utilized for 4D-MR image reconstruction. A parallel contour editing approach was employed in the ATS workflow. Intravoxel incoherent motion (IVIM) and T2 mapping sequences were acquired during adaptive planning in both ATP and ATS workflows for treatment response monitoring. Adaptive plans were delivered under real-time cine image motion monitoring. Results: The shortest 4D-MRI time-to-image was the motion averaged image, followed by mid position and respiratory binned images. In this cohert of patients, 50% of treatments utilized the ATS workflow; the remaining treatments utilized the ATP workflow. Mid-position images were utilized as daily planning images for two of the eleven patients. The mean daily adaptive plan secondary dose calculation and ArcCheck 3D Gamma passing rates were 97.5% (92.1–100.0%) and 99.3% (96.2–100.0%), respectively. The median overall treatment times for abdominal SBRT was 46 and 62 min for ATP and ATS workflows, respectively. Conclusion: We have successfully implemented and utilized a 4D-MRI driven MRgOART process with ATP and ATS workflows for free-breathing abdominal SBRT on a 1.5 T Elekta Unity MR-Linac.